Psyhoemotional Aspects for Creative Potential Development within the Framework of Schoolchildren Informational Culture Environment - Abitova, Gulbanu T.; Bapayeva, Mariyam K.; Koksheeva, Zaini T.; Kapenova, Anar A.; Utepbergenova, Zeynekul D. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: In the process of creativity, the child develops intellectually and emotionally, determines its attitude towards life and its place in life, acquires the experience of collective interaction, improves its skills in working with various tools and materials. Background: At present times, which most researchers refer to as the era of “creative information culture”, the potential for creative development of students is of interest to both scientists and teachers. This paper considers creativity as a child’s sense-creating ability, as a student’s ability to form a model of the surrounding microcosm in the consciousness, which most often develops based on reading and processing information. This feature determines the uniqueness of the value-semantic attitude of children with inclusion to the world in general and to information, in particular. Method: The study used materials from textbooks and manuals. Learning programs for children with developmental standards were studied. The level of students’ creative thinking was tested. Methods for its development are derived. Results: Various sources of information make up such a picture of the child’s world in which a certain value-semantic core is gradually formed. On extensive material through comparative analysis it is proved that the creative component is characterised by the manifestation of fantasy and imagination in all the diverse informational aspects; the need for new information; dedication to the process of cognition; the desire to master the basics of creative search activity; manifestation of independence in the selection of means and methods of cognition; desire for co-creation with adults. In the process of creativity, the child develops intellectually and emotionally, determines his attitude to life and his place in it, acquires the experience of collective interaction, and improves his skills in working with various tools and materials. Conclusion: According to the author, it is an artistic and creative activity that actualises the inner potential of the child, reveals his creative abilities, allows us to define the artistic and creative self-realisation of a pre-schooler as an organised process of targeted pedagogical.